2013
DOI: 10.1016/j.taap.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional deficiency of aryl hydrocarbon receptor augments oxygen toxicity-induced alveolar simplification in newborn mice

Abstract: Hyperoxia contributes to the development of bronchopulmonary dysplasia (BPD) in premature infants. New BPD is characterized as having alveolar simplification. We reported previously that aryl hydrocarbon receptor (AhR) deficiency increased susceptibility to hyperoxic lung injury in adult mice, and this was associated with decreased expression of cytochrome P450 1A enzymes and increased lung inflammation. Whether AhR protects newborn mice against hyperoxia-induced alveolar simplification is unknown. Thus, we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…This phenomenon might be a protective responsive to oxidative stress because of its striking resemblance to the effects of hyperoxia on the “classic” AOE such as superoxide dismutase, glutathione peroxidase, glutathione reductase, and catalase (Ho et al , 1996; Clerch, 2000). Furthermore, decreased expression of phase I and II enzymes in newborn AhRd mice compared to wild type mice was associated with increased hyperoxic lung injury in our previous study (Shivanna et al , 2013), which suggests that the effects of hyperoxia on these enzymes are a compensatory rather than a contributory response. In our study, there were no significant differences in expression of phase II enzymes between air-exposed AhR-sufficient and –deficient cells.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This phenomenon might be a protective responsive to oxidative stress because of its striking resemblance to the effects of hyperoxia on the “classic” AOE such as superoxide dismutase, glutathione peroxidase, glutathione reductase, and catalase (Ho et al , 1996; Clerch, 2000). Furthermore, decreased expression of phase I and II enzymes in newborn AhRd mice compared to wild type mice was associated with increased hyperoxic lung injury in our previous study (Shivanna et al , 2013), which suggests that the effects of hyperoxia on these enzymes are a compensatory rather than a contributory response. In our study, there were no significant differences in expression of phase II enzymes between air-exposed AhR-sufficient and –deficient cells.…”
Section: Discussionmentioning
confidence: 55%
“…Recently, we also observed that newborn AhR dysfunctional (AhRd) mice have a similar susceptibility to hyperoxic lung injury that is associated with decreases in the expression of phase I (CYP 1A) and phase II (NQO1 and microsomal glutathione S-transferase 1) AOE (Shivanna et al , 2013). Additionally, other investigators have found that AhR-deficient mice have an increased inflammatory response in their lungs on exposure to cigarette smoke or bacterial endotoxin (Thatcher et al , 2007; Baglole et al , 2008; de Souza et al , 2014), suggesting that AhR activation mediates processes suppressing lung inflammation.…”
Section: Introductionmentioning
confidence: 96%
“…Studies from our and other laboratories have reported that AhR and its downstream target, CYP1A enzymes, may be a crucial regulator of pulmonary and hepatic oxidant stress and inflammation in mice through the induction of several detoxifying enzymes or via "cross-talk" with other signal transduction pathways (Jiang et al, 2004;Thatcher et al, 2007;Baglole et al, 2008; Rico de dmd.aspetjournals.org Souza et al, 2011;Shivanna et al, 2011bShivanna et al, , 2013. However, the prototypical inducers such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and MC are unsuitable for clinical use because of their well known toxicities.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent studies have demonstrated an attenuating effect of CYP1A1 inducers on hyperoxic lung injury both in vitro [10,24] as well as in vivo [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the importance of cytochrome P450 enzymes as well as the aryl hydrocarbon receptor (AhR) has been demonstrated in the metabolism of a number of endogenous and exogenous compounds as well as for oxygen-induced toxicity [10][11][12][13]. When a ligand binds, AhR is translocated to the nucleus, where it dimerizes with the aryl hydrocarbon nuclear translocator (ARNT).…”
mentioning
confidence: 99%